2021
DOI: 10.1080/19420889.2021.1972523
|View full text |Cite
|
Sign up to set email alerts
|

The search for molecular mimicry in proteins carried by extracellular vesicles secreted by cells infected with Plasmodium falciparum

Abstract: Red blood cells infected with Plasmodium falciparum secrete extracellular vesicles in order to facilitate the survival and infection of human cells. Various researchers have studied the composition of these extracellular vesicles and identified the proteins contained inside. In this work, we used that information to detect potential P. falciparum molecules that could be imitating host proteins. We carried out several searches to detect sequences and structural similarities between the parasite and host. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Increased exposure of highly sialylated N ‐glycans on Pf EVs supports the hypothesis that Pf exploits a similar mechanism to dampen the host immune response by interaction with host cells and downstream immune modulation. This possible mechanism of EV‐mediated molecular mimicry by Pf was proposed previously at the protein level (Armijos‐Jaramillo et al., 2021 ), but no evidence for the involvement of glycans in this process has been provided until now. However, altered EV glycosylation was reported in other diseases to dramatically influence EV‐cell interactions, impacting receptor interaction and cellular uptake (Dusoswa et al., 2019 ; Whitehead et al., 2020 ; Williams et al., 2019 ).…”
Section: Discussionmentioning
confidence: 64%
“…Increased exposure of highly sialylated N ‐glycans on Pf EVs supports the hypothesis that Pf exploits a similar mechanism to dampen the host immune response by interaction with host cells and downstream immune modulation. This possible mechanism of EV‐mediated molecular mimicry by Pf was proposed previously at the protein level (Armijos‐Jaramillo et al., 2021 ), but no evidence for the involvement of glycans in this process has been provided until now. However, altered EV glycosylation was reported in other diseases to dramatically influence EV‐cell interactions, impacting receptor interaction and cellular uptake (Dusoswa et al., 2019 ; Whitehead et al., 2020 ; Williams et al., 2019 ).…”
Section: Discussionmentioning
confidence: 64%
“…For instance, several viruses express proteins with tertiary structure similarity, but undetectable sequence similarity to human Bcl-2, and interfere with regulation of apoptosis (Kvansakul et al, 2007; Westphal et al, 2007). Similarly, in Plasmodium falciparum , a search of parasite proteins targeted to host extracellular vesicles revealed that at least eight shared unexpected and significant tertiary structure similarity with host proteins (Armijos-Jaramillo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We expect that most, if not all, other bacterial and eukaryotic pathogen species will have worse coverage. Proteome-wide searches for host-parasite molecular mimicry at the level of tertiary structure depended on in silico predictions that were of inconsistent quality (Armijos-Jaramillo et al, 2021). The prediction of tertiary protein structures from amino acid sequences has seen a much-publicised boon, in no small part to the development of AlphaFold (Ronneberger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several viruses express proteins with tertiary structure similarity, but undetectable sequence similarity, to human Bcl-2, and interfere with regulation of apoptosis (Kvansakul et al, 2007;Westphal et al, 2007). Similarly, in Plasmodium falciparum, a search of parasite proteins targeted to host extracellular vesicles revealed that at least eight shared unexpected and significant tertiary structure similarity with host proteins (Armijos-Jaramillo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We expect that most, if not all, other bacterial and eukaryotic pathogen species will have worse coverage. Proteome-wide searches for host-parasite molecular mimicry at the level of tertiary structure depended on in silico predictions that were of inconsistent quality (Armijos-Jaramillo et al, 2021). The prediction of tertiary protein structures from amino acid sequences has seen a much-publicized boon, in no small part to the development of AlphaFold (Ronneberger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%